Herbicide Resistance in Phalaris Species: A Review - Javid Gherekhloo (MDPI AG, 2021)
Weeds, such as Phalaris spp., can drastically reduce the yield of crops, and the evolution of resistance to herbicides has further exacerbated this issue. Thus far, 23 cases of herbicide resistance in 11 countries have been reported in Phalaris spp., including Phalaris minor Retz., Phalaris paradoxa L., and Phalaris brachystachys L., for photosystem II (PS-II), acetyl-CoA carboxylase (ACCase), and acetolactate synthase (ALS)-inhibiting herbicides. This paper will first review the cases of herbicide resistance reported in P. minor, P. paradoxa, and P. brachystachys. Then, the mechanisms of resistance in Phalaris spp. are discussed in detail. Finally, the fitness cost of herbicide resistance and the literature on the management of herbicide-resistant weeds from these species are reviewed.